Under-frequency Load Shedding technique considering response based for islanding distribution network connected with mini hydro / Salmah Sahdan - Sahdan, Salmah (2014)
Under-frequency Load Shedding (UFLS) is a technique to remove the unbalance load demand over generation supply in some part of the system. The application of this technique will maintain the power system stability. UFLS operate successful on the grid connected rather than islanding network system. This is due to islanded system is not as strong as grid connected, thus a suitable UFLS scheme is required. The aim of this research is to design UFLS considering response based for an islanded system.